Pengaruh Pengaplikasi dan Pemasaran Digital Terhadap Penjualan Produk UMKM Panganan Lokal: Studi Kasus Rumah Bangkit Fafin - Cindy Nidaul Husna; Panji Satya Mahadireza; Intan Permatasari; Hasti Setya Utami; Suryo Suminar (EBISMAN eBisnis Manajemen, 2024)
In the rapidly evolving digital era, the impact of digital marketing on the market acceptance of local food products from SMEs (Small and Medium Enterprises) has become a critical topic. To maintain competitiveness and increase revenue, SMEs need to adapt to the shifting consumption patterns in this era. Implementing digital marketing strategies is one of the solutions that can be adopted by SMEs. Utilizing social media, email, and websites in these strategies can raise brand awareness and drive sales growth. This research aims to analyze the digital marketing strategies implemented by UMKM Kue Bangkit Fafin in Serang City to increase sales of their local food products.